Determinants of Women’s Participation in Small-Scale Vegetable Farming in Cabintan, Ormoc City, Leyte - Ray Ann Rosos; Ana Liza M. Recto; Maria Hazel I. Bellezas; Zyra May H. Centino (Review of Socio-Economic Research and Development Studies, 2023)
Small-scale vegetable farming is relatively known to be the major source of income among villages residing in Cabintan, Ormoc, City Leyte. However, very few studies articulating women’s participation and role in small-scale vegetable farming are available in this area. The existing studies are mostly about aggregate production and farmers’ practices. This study aims to fill that gap by examining women’s involvement in farming activities and determine factors that influence their participation. A total of 146 women were randomly selected and interviewed. The women’s participation in small-scale vegetable farming was categorized as active or less active. Results show that more than eighty percent (83.7%) of the women respondents are considered active in farming activities while only around 15.6% are considered less active. Regarding farming activities, women are mostly involved in the marketing aspect but spend less time in land preparation. The multiple linear regression analysis shows land tenure influences women’s decision to participate in farming. In addition, women are more likely to be involved in farming if the husband is a farmer as well. This implies that government programs aiming to encourage women’s participation should also consider their husbands’ occupations. In addition, continued capacity-building programs were emphasized by women as essential in dealing with challenges in small-scale vegetable production.